Analysis of 500W 2000rpm switched reluctance motor using 2D FEMM / Intan Zurina Ismail - Ismail, Intan Zurina (2010)
This paper presents the idea of using the FEMM simulation software as an alternative to other simulation to other simulation today. The FEMM is used to simulate the single-phase Switched Reluctance Motor in order to gain result of the motor and to compare the outcome this software. The single phase Switched Reluctance Motor is a simplest electrical machine to construct where the motor only consist of the excitation winding stator and magnetic rotor with saliency. The single-phase Switched Reluctance Motor is easy to construct by using this software.